Tumpang Sari antara Jagung dan Cabai Rawit Sebagai Olahan Tani di Kabawetan - Mekar Ria Pangaribuan; Meriani Meriani; Abditama Srifitriani (Universitas Prof. Dr. Hazairin, SH, 2021)
Intercropping between Corn and Cayenne Pepper as Processed Farmers in Kabawetan The partner's land is in Kabawetan Village, Kepahiang Regency and has not been used optimally. It is suitable for intercropping between corn and cayenne pepper. How to cultivate partner land to be more productive was the goal of the activity. The method was a community assistance model through training and workshops. The result was an intercropping system was carried out through: 1) land processing, 2) seedling, 3) planting, 4) fertilization, 5) taking care the plants, and 6) harvesting. The production costs consisted of 1) seeds for an area of 12 m x 20 m wass 550.000 IDR, labor for 3 working day was 240,000 IDR, 15 sacks of fertilizer were 300,000 IDR, and mulch was 600,000 IDR. The corn was harvested every 3 months, while the cayenne pepper was harvested every 15 days. The cultivation system setup for 7 years with the used capital was 1,690,000 IDR. The corn planting started from the left side of the bed as a protection for chilies. Corn produced are around 500 plants x 2 kg x 4,000 IDR. Cayenne pepper is planted on the right side of the bed when the corn was 2 months old. The chilies were sowed first before planting on the mulching land. Cayenne pepper harvested every 15 days during the 7 years’ project period. There were about 3000 stems x 1.5 kg stem-1 x 20,000 IDR kg-1. Intercropping system can improve the welfare of partners.